ATTITUDES OF STUDENTS OF DIFFERENT STUDY PROGRAMMES IN HIGH SCHOOL TO PERCEPTION PERSONAL COMPUTER - CHRÁSKOVÁ, Marie; CHRÁSKA, Miroslav (Trends in education, 2010)
This paper deals with research, which compared attitudes of students of different study programmes in high school to perception personal computer.
Keywords: semantic differential; attitudes of students in high school to perception personal computer; Analysis of Variance